KEYNOTE-590: Phase III study of first-line chemotherapy with or without pembrolizumab for advanced esophageal cancer. (8th February 2019) - Kato, Ken; Shah, Manish A; Enzinger, Peter; Bennouna, Jaafar; Shen, Lin; Adenis, Antoine; Sun, Jong-Mu; Cho, Byoung Chul; Özgüroğlu, Mustafa; Kojima, Takashi; Kostorov, Vladimir; Hierro, Cinta; et al.
Background: Treatment options for patients with advanced esophageal or esophagogastric junction (EGJ) cancer are limited. Current guidelines for first-line treatment of advanced esophageal or EGJ cancer recommend chemotherapy containing a platinum and a fluoropyrimidine agent. Pembrolizumab demonstrated antitumor activity in previously treated patients with advanced esophageal cancer and in patients with gastroesophageal junction cancer.Aim: To describe the design and rationale for the randomized, double-blind, placebo-controlled Phase III KEYNOTE-590 study, which will be conducted to investigate pembrolizumab in combination with chemotherapy as first-line treatment in patients with advanced esophageal or EGJ cancer. Clinical trial registry & ID: ClinicalTrials.gov : NCT03189719.